Pemodelan Kesesuaian Habitat Katak Serasah (Leptobrachium hasseltii Tschudi 1838) dengan Sistem Informasi Geografis di Pulau Jawa - Anika Putri; Mirza Dikari Kusrini; Lilik Budi Prasetyo (Graduate School Bogor Agricultural University (SPs IPB), 2020)
Hasselt’s litter frogs (Leptobrachium hasseltii Tschudi 1838) is a wide spread species in Java and Sumatra, but there is no specific distribution map for this species. The purpose of this study is to identify the distribution of hasselt’s litter frogs in Java and examine the suitability of it’s using maxent. We used presence data and environment variables consisting of elevation, slope, NDVI (Normalized Difference Vegetation Index), distance from the river, temperature, precipitation, and land cover to evelop the distribution model of this species. Hasselt’s litter frogs in Java depends on forested area with a wide range of elevation (lowland to mountain forests), moderate slope, temperature between 20-21oC and rainfall over 2500 mm/year. The highest number of frogs are found in secondary forest land cover, as supported by NDVI values between 0.8 to 0.9 and relatively close to the river. Habitat model constructed are robust with AUC (Area Under Curve) value of 0.951. Environmental variables that most affectted habitat for hasselt’s litter frog are land cover, temperature, and slope.